Актуальність використання соціальних сервісів викладачем вищої школи - Твердохлєбова, Наталя Євгеніївна; Мовмига, Наталія Євгенівна; Євтушенко, Наталія Сергіївна; Семенов, Євгеній Олександрович (Переяслав-Хмельницький державний педагогічний університет ім. Григорія Сковороди, 2017)
Проведений аналіз дослідження соціальних сервісів, на базі яких створюється персональне навчальне середовище освітянина. Виділені соціальні сервіси, програми, інструменти Інтернет, за допомогою яких забезпечуються комфортні умови для здійснення професійної діяльності викладача, а саме: пошук джерел інформації, створення, редагування, зберігання, подача навчальних матеріалів, їх розповсюдження, публікація в мережі, інформаційне забезпечення навчального процесу.

The article analyzes the research of social services, on the basis of which creates a personalized learning environment for the teacher. The task of the modern teacher-tutor - not only to give the student knowledge in accordance with the approved curriculum, but also to provide him vital skills information, the ability to communicate effectively with colleagues, including through the Internet, and continuously develop and study independently. Content management skills are useful in education - to provide professional, pedagogical and technological activity of the teacher. Offered social services, programs, internet tools with which provided favorable conditions for the exercise of professional activity of the teacher, namely the search for sources of information, creation, editing, storage, supply of teaching materials, their distribution and publication on the web, information support of the educational process.
Relevance of using social service high school teacher
Keywords: соціальні сервіси; інтернет технології; хмарні технології; персональне навчальне середовище; куратор змісту; інформаційний аналітик; personal learning environment; social services; cloud-based technology; content curator; information analyst